2018
DOI: 10.1083/jcb.201804132
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screen identifies TMEM41B as a gene required for autophagosome formation

Abstract: Macroautophagy is an intracellular degradation process that requires multiple autophagy-related () genes. In this study, we performed a genome-wide screen using the autophagic flux reporter GFP-LC3-RFP and identified as a novel gene. TMEM41B is a multispanning membrane protein localized in the endoplasmic reticulum (ER). It has a conserved domain also found in vacuole membrane protein 1 (VMP1), another ER multispanning membrane protein essential for autophagy, yeast Tvp38, and the bacterial DedA family of puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
191
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 54 publications
(68 reference statements)
16
191
1
Order By: Relevance
“…Recent studies have shown that Stasimon is an ER-resident six-transmembrane pass protein that is essential for mouse embryonic development (Van Alstyne et al, 2018b) and functions in autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). However, we found no evidence for overt autophagy dysregulation in motor circuit neurons of SMA mice.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Recent studies have shown that Stasimon is an ER-resident six-transmembrane pass protein that is essential for mouse embryonic development (Van Alstyne et al, 2018b) and functions in autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). However, we found no evidence for overt autophagy dysregulation in motor circuit neurons of SMA mice.…”
Section: Discussioncontrasting
confidence: 68%
“…We then analyzed by Western blot the levels of the autophagy proteins p62 and LC3 in WT and StasRNAi NIH3T3 cells under basal conditions and following autophagy induction with serum starvation or inhibition by Bafilomycin A1 treatment ( Figure S2B). We found that the levels of p62 and lipidated LC3 (LC3-II) were moderately increased in Stasimon-deficient relative to WT cells, consistent with dysregulation of autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). However, Western blot analysis showed no changes in the levels of both p62 and LC3 in spinal cords from WT and SMA mice at P11 ( Figure S2C).…”
Section: Stasimon Contributes To Motor Neuron Degeneration In Sma Micementioning
confidence: 71%
See 2 more Smart Citations
“…However, recent studies have increasingly emphasized the existence of systems controlling and executing autophagy in mammalian cells that are quite different from those in yeast [3]. Among wellaccepted examples, are several autophagy factors absent in yeast that have been identified in organisms from C. elegans to H. sapiens, including ATG101 [4], FIP200 [5], VMP1 [6], EPG5 [7], Stx17 [8,9], and TMEM41B [10][11][12].…”
Section: Introductionmentioning
confidence: 99%